Randomized Trial Evaluating Clinical Impact of RAPid IDentification and Susceptibility Testing for Gram-negative Bacteremia: RAPIDS-GN. (6th May 2020) - Banerjee, Ritu; Komarow, Lauren; Virk, Abinash; Rajapakse, Nipunie; Schuetz, Audrey N; Dylla, Brenda; Earley, Michelle; Lok, Judith; Kohner, Peggy; Ihde, Sherry; Cole, Nicolynn; Hines, Lisa; et al.
Abstract: Background: Rapid blood culture diagnostics are of unclear benefit for patients with gram-negative bacilli (GNB) bloodstream infections (BSIs). We conducted a multicenter, randomized, controlled trial comparing outcomes of patients with GNB BSIs who had blood culture testing with standard-of-care (SOC) culture and antimicrobial susceptibility testing (AST) vs rapid organism identification (ID) and phenotypic AST using the Accelerate Pheno System (RAPID). Methods: Patients with positive blood cultures with Gram stains showing GNB were randomized to SOC testing with antimicrobial stewardship (AS) review or RAPID with AS. The primary outcome was time to first antibiotic modification within 72 hours of randomization. Results: Of 500 randomized patients, 448 were included (226 SOC, 222 RAPID). Mean (standard deviation) time to results was faster for RAPID than SOC for organism ID (2.7 [1.2] vs 11.7 [10.5] hours; P  < .001) and AST (13.5 [56] vs 44.9 [12.1] hours; P  < .001). Median (interquartile range [IQR]) time to first antibiotic modification was faster in the RAPID arm vs the SOC arm for overall antibiotics (8.6 [2.6–27.6] vs 14.9 [3.3–41.1] hours; P  = .02) and gram-negative antibiotics (17.3 [4.9–72] vs 42.1 [10.1–72] hours; P  < .001). Median (IQR) time to antibiotic escalation was faster in the RAPID arm vs the SOC arm for antimicrobial-resistant BSIs (18.4 [5.8–72] vs 61.7 [30.4–72] hours; P  = .01). There were no differences between the arms in patient outcomes. Conclusions: Rapid organism ID and phenotypic AST led to faster changes in antibiotic therapy for gram-negative BSIs. Clinical Trials Registration: NCT03218397. Abstract : This randomized, controlled trial demonstrates that compared with conventional testing, a rapid phenotypic antibiotic susceptibility testing method implemented together with antibiotic stewardship can facilitate significantly faster antibiotic modifications during treatment of gram-negative bloodstream infections.